Phenotype and function of peripheral blood γδ T cells in HIV infection with tuberculosis - Zou, Shi; Xiang, Yanni; Guo, Wei; Zhu, Qi; Wu, Songjie; Tan, Yuting; Yan, Yajun; Shen, Ling; Feng, Yong; Liang, Ke (Frontiers in Cellular and Infection Microbiology, 2022)
Although γδ T cells play an important role in immunity against Human Immunodeficiency Virus (HIV) or Mycobacterium tuberculosis (MTB), they are poorly described in HIV infection with tuberculosis (TB). The phenotypic and functional properties of peripheral blood γδ T cells in patients with HIV/TB co-infection were analyzed in comparison to healthy controls and patients with HIV mono-infection or TB by direct intracellular cytokine staining (ICS). The percentage of Vδ1 subset in HIV/TB group were significantly higher than that in TB group, while decreased frequency of the Vδ2 and Vγ2Vδ2 subsets were observed in HIV/TB group than that in TB group. The percentage of CD4+CD8- Vδ2 subset in HIV/TB group was markedly lower than that in TB group. However, the percentage of CD4+CD8+ Vδ2 subset in HIV/TB group was markedly higher than HIV group or TB group. Lower percentage TNF-α and higher percentage of IL-17A of Vδ2 subset were observed in HIV/TB group than that in HIV mono-infection. The percentage of perforin producing Vδ2 subset was significantly lower in HIV/TB group than that in HIV group and TB group. Our data suggested that HIV/TB co-infection altered the balance of γδ T cell subsets. The influence of HIV/TB co-infection on the function of γδ T cells to produce cytokines was complicated, which will shed a light on further investigations on the mechanisms of immune response against HIV and/or MTB infection.